Nugormesese : An Indigenous Basis of Social Capital in a West African Community - World Bank (Washington, DC, 2012)
The primary objective of this article is to present nugormesese as an indigenous mechanism of social capital in Buem-Kator, a farming community on the Ghana side of the Ghana-Togo border area. The concept of social capital will be minimally defined to refer to the capability of social norms and customs to hold members of a group together by effectively setting and facilitating the terms of their relationships. Unlike physical capital (machineries, bank accounts, etc.) and human capital (knowledge, skills, etc), social capital is a relational factor or social resource that sustainably facilitates collective action for achieving mutually beneficial ends.